Modal identification of bridge 44 of the Carajás railroad and numerical modeling using the finite element method. - Silva, Marcela Santos da (2020)
Regular use and the effects of time can affect the behavior of a structure. Over time, problems such as the occurrence of small fissures, oxidation of steel elements, and excessive displacements at some points may arise in a structure. In this context, the monitoring of structures through experimental tests has gained more importance, because it allows for the identification of the dynamic characteristics (natural frequencies, mode shapes, and damping rate) of structures. The dynamic characteristics can be obtained through forced vibration tests, which are based on measuring the response of a structure subjected to an excitation of known magnitude, or through tests in which only the structural response is measured, such as free vibration and ambient vibration tests. The present study aims to identify the modal parameters of bridge 44 of the Carajás Railroad, using experimental data obtained on site by monitoring the vibration caused by a group of people jumping, and it compares them with the results obtained through numerical modeling performed using the finite element method, developed in CSiBridge. The modal parameters were obtained using the commercial software ARTeMIS Modal, and stochastic subspace identification was used for modal identification.